2019
DOI: 10.1177/1753425919889392
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal therapy increases neutrophil extracellular trap degradation

Abstract: In periodontitis, polymorphonuclear leucocytes (PMNs) are activated. They entrap and eliminate pathogens by releasing neutrophil extracellular traps (NETs). Abnormal NET degradation is part of a pro-inflammatory status, affecting co-morbidities such as cardiovascular disease. We aimed to investigate the ex vivo NET degradation capacity of plasma from periodontitis patients compared to controls (part 1) and to quantify NET degradation before and after periodontal therapy (part 2). Fresh NETs were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
10
0
3
Order By: Relevance
“…A key to this process is that the mechanism of NET removal is similar to that of apoptosis, whereby macrophages do not release pro-inflammatory cytokines [59]. Recently it has been reported that NET degradation is increased in treated periodontitis patients, what indicates that NET degradation contributes to a decreased pro-inflammatory state [60,61].…”
Section: Removal Of Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key to this process is that the mechanism of NET removal is similar to that of apoptosis, whereby macrophages do not release pro-inflammatory cytokines [59]. Recently it has been reported that NET degradation is increased in treated periodontitis patients, what indicates that NET degradation contributes to a decreased pro-inflammatory state [60,61].…”
Section: Removal Of Netsmentioning
confidence: 99%
“…The formation of NETs could promote thrombosis via histones [61]. NETs in combination with platelets may damage the blood vessels during sepsis, destroying endothelial cells and causing vascular occlusions [76,89].…”
Section: Role Of Nets In Systemic Diseasesmentioning
confidence: 99%
“…Multivariate logistic regression analysis showed that the peripheral blood NET level was significantly positively associated with moderate to severe PD (Kaneko et al, 2018). Degradation of NETs in plasma is increased after periodontal therapy in PD patients (Moonen et al, 2020). Periodontal pathogens and excessive NETs produced during PD may participate in the progression of AS after entering the circulation.…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%
“…2016; Doke et al, 2017;Obama et al, 2019;Moonen et al, 2020). There are other DNA releasing activities, such as necrosis, which would confound the results.…”
Section: Measurement and Removal Of Netsmentioning
confidence: 99%